2020
DOI: 10.1029/2020wr027403
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling Effects of the Pore‐Size Correlation Length on the Two‐Phase Flow and Solute Transport Properties: GPU‐based Pore‐Network Modeling

Abstract: Continuum‐scale models for two‐phase flow and transport in porous media are based on the empirical constitutive relations that highly depend on the porous medium heterogeneity at multiple scales including the microscale pore‐size correlation length. The pore‐size correlation length determines the representative elementary volume and controls the immiscible two‐phase invasion pattern and fluids occupancy. The fluids occupancy controls not only the shape of relative permeability curves but also the transport zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 73 publications
1
27
0
Order By: Relevance
“…None of the commonly used theories, including the mobile–immobile model (MIM) ( 22 ), the multirate mass transfer (MRMT) ( 23 ), and continuous time random walk ( 24 ) models include two-phase flow formulations in their theoretical developments. To date, the capability of such models to match the experimental data using inverse modeling has been tested, but the physical consistency of such models is still open to be evaluated ( 25 , 26 ).…”
mentioning
confidence: 99%
“…None of the commonly used theories, including the mobile–immobile model (MIM) ( 22 ), the multirate mass transfer (MRMT) ( 23 ), and continuous time random walk ( 24 ) models include two-phase flow formulations in their theoretical developments. To date, the capability of such models to match the experimental data using inverse modeling has been tested, but the physical consistency of such models is still open to be evaluated ( 25 , 26 ).…”
mentioning
confidence: 99%
“…The range of the variance, which describes the correlation of the field, is shown to increase from A to C ( Figure 6). Recently, An et al (2020) showed that for porous media applications the correlation length of the pore size distribution should be 1/20th of the minimum sample dimension to guarantee an REV. While we do not attempt to define an REV of a single fracture here, we want to ensure to that our simulations are not sensitive to different realizations of the wetting patterns.…”
Section: Parameter Determination and Model Verificationmentioning
confidence: 99%
“…We provide a brief explanation of the key concepts of dynamic two‐phase pore network modeling here. The first step in pore network modeling is to extract or generate the pore network morphology (An, Hasan, et al, 2020; Raeini et al, 2017). The topology of the network can be extracted using different methods among which the medial axis‐based method is a robust one (Joekar Niasar et al, 2009).…”
Section: Dynamic Two‐phase Pore Network Modelingmentioning
confidence: 99%
“…The direct pore‐scale simulation methods are computationally too demanding compared to the pore network models. This challenge becomes prohibitive if the simulation of multiphase flow is aimed at the REV scale of a porous medium (An, Hasan et al, 2020; Shams et al, 2018). Moreover, none of these models has been able to achieve a superior predictive capability compared to others (Zhao et al, 2019), and in some cases pore network modeling has been successful in predicting pore‐scale phenomena (Joekar Niasar et al, 2009; Oostrom et al, 2016).…”
Section: Introductionmentioning
confidence: 99%